The Effects of Surgical Technique in Total Knee Arthroplasty for Varus Osteoarthritic Knee on the Rotational Alignment of Femoral Component: Gap Balancing Technique versus Measured Resection Technique - Kim, Chang-Wan; Lee, Chang-Rack; Gwak, Heui-Chul; Kim, Jung-Han; Kwon, Yong-Uk; Kim, Doo-Yeol (The Journal of Knee Surgery, 2020)
Few studies have compared the accuracy of femoral component rotation in the measured resection technique according to the preoperative computed tomography (CT) and gap balancing technique. The aim of this study was to evaluate whether there is a difference in accuracy and outlier incidence of femoral component rotation between gap balancing and measured resection techniques with or without preoperative CT and to evaluate the difference in patellofemoral alignment on simple radiographs and clinical outcomes. In this retrospective study, we evaluated femoral component rotation angle on the clinical and surgical transepicondylar axis (FCRA-cTEA and FCRA-sTEA, respectively), patellar tilt angle, lateral patellar displacement, and patient-reported outcomes in the gap balancing technique (Group 1) and in the measured resection technique without (Group 2) and with (Group 3) preoperative CT. A total of 163 total knee arthoplasty (TKA) replacements were included in this study. Average FCRA-cTEA was −3.4 ± 2.6, −2.8 ± 2.1, and −1.8 ± 2.3 degrees in groups 1 to 3, respectively (p = 0.002). Average FCRA-sTEA was −0.2 ± 2.7, 0.5 ± 2.4, and 1.5 ± 2.1 degrees, respectively (p = 0.001). In an outlier analysis that evaluated femoral component rotation using cTEA as reference, no significant difference was observed between the three groups (40.8, 37.3, and 23.7%, respectively, p = 0.133). When sTEA was used as a reference, groups 1 and 3 showed an outlier incidence of 8.2 and 8.5%, respectively, whereas this incidence was as high as 23.5% in group 2 (p = 0.030). No statistically significant group difference in patellofemoral alignment and patient-reported outcome was observed. In the measured resection technique with preoperative CT, the femoral component was externally rotated approximately 1 degree more than in the gap balancing or measured resection technique without preoperative CT. However, the difference in FCRA among the three techniques was not linked to the difference in patellofemoral alignment or patient-reported outcomes.
Keywords: total knee arthroplasty; measured resection; gap balancing; rotation